Educational Transformation Through Virtual Learning Environment (VLE) as an Effort to Improve Students' Critical Thinking Competence - Sri Setiawaty; Riska Imanda; Reza Putra (Postgraduate, University of Mataram, 2023)
Industrial revolution 4.0 in the 21st century, many countries have made their country's roadmaps to be able to survive in the midst of dynamic changes. The 21st century is marked by information that can be accessed by anyone, anytime and anywhere, computing or the use of robots, automation or work that can be done routinely and communication that becomes unlimited in every aspect of people's lives. The purpose of this research is to, 1) find out the feasibility of the developed Virtual Learning Environment (VLE) media for use in learning, 2) find out the perceptions of teachers and students towards the developed Virtual Learning Environment (VLE). This research and development (R&D) research adapt the 4-D development model (define, design, develop and desiminate). The results of this research, namely the validity of the learning media developed was obtained from the assessment results with an average percentage of 93% in the 'Very Good' category, the quality of the learning media developed obtains assessment results with an average percentage of 92% in the category